2014
DOI: 10.1016/j.cytogfr.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation in Toll-like receptor signaling

Abstract: There is a wealth of knowledge about how different Ser/Thr protein kinases participate in Toll-like receptor (TLR) signaling. In many cases, we know the identities of the Ser/Thr residues of various components of the TLR-signaling pathways that are phosphorylated, the functional consequences of the phosphorylation and the responsible protein kinases. In contrast, the analysis of Tyr-phosphorylation of TLRs and their signaling proteins is currently incomplete, because several existing analyses are not systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 91 publications
(103 reference statements)
1
83
0
Order By: Relevance
“…Tyrosine phosphorylation results in the recruitment of the phosphorylase kinase, such as Ser/Thr kinase and PI3K, to the signaling complex, a step that is essential for the activation of downstream transcription factors (11). Tyrosine phosphorylation then provides docking sites for other proteins (11). Structural analysis indicates that both TRIF and TRAM TIR domains form a BB-loop-mediated homodimer (30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tyrosine phosphorylation results in the recruitment of the phosphorylase kinase, such as Ser/Thr kinase and PI3K, to the signaling complex, a step that is essential for the activation of downstream transcription factors (11). Tyrosine phosphorylation then provides docking sites for other proteins (11). Structural analysis indicates that both TRIF and TRAM TIR domains form a BB-loop-mediated homodimer (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TIRAP underwent tyrosine phosphorylation at the residues within its TIR domain following LPS stimulation, and this modification initiated a con- formational change in the TIR domain of TIRAP (12,13), thereby leading to activation of downstream signals. Tyrosine phosphorylation results in the recruitment of the phosphorylase kinase, such as Ser/Thr kinase and PI3K, to the signaling complex, a step that is essential for the activation of downstream transcription factors (11). Tyrosine phosphorylation then provides docking sites for other proteins (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, TLR4 signaling activated in MCs seems to exclusively depend on the function of the MyD88 adapter, because the expression of elements of the MyD88-independent pathway was not detected in bone marrow-derived MCs (BMMCs) (18,19). The participation of Src family kinases in TLR4 signaling in immune cells was suggested (20), and Lyn kinase was shown to participate in the induction of cytokine synthesis after TLR4 triggering in monocytes (21) and MCs (22,23).…”
Section: /2mentioning
confidence: 99%